INNOVATION MANAGEMENT TECHNIQUES AND TOOLS: ITS IMPACT ON FIRM INNOVATION PERFORMANCE - ALBORS-GARRIGOS, JOSE; IGARTUA, JUAN IGNACIO; PEIRO, ANGEL (International journal of innovation management, 2018)
Innovation management is a subject that raises the interest of academics and practitioners in the field of management. However, the academic literature is scarce regarding the details of implementing it in a systemic and routinised way. Additionally, although there are multiple tools and models to apply it at a firm level, there is little information concerning its effectiveness. The purpose of this paper is to fill this research gap by analysing how the utilisation of Innovation Management Techniques (IMTS) influences the innovation performance of firms. The research was based on a large and representative sample of industries in the Basque Region in Northeast Spain. The primary conclusions drawn from the research are that IMTS have a definite positive impact on the firm’s innovation results, and some of them have a stronger influence, with a significant impact on incremental innovation; the latter results will affect the radical innovation performance of the companies. Additionally, it has been concluded that the industry environment has a strong moderating influence on this relationship.